2009
DOI: 10.4049/jimmunol.0900327
|View full text |Cite
|
Sign up to set email alerts
|

12/15-Lipoxygenase Counteracts Inflammation and Tissue Damage in Arthritis

Abstract: Eicosanoids are essential mediators of the inflammatory response and contribute both to the initiation and the resolution of inflammation. Leukocyte-type 12/15-lipoxygenase (12/15-LO) represents a major enzyme involved in the generation of a subclass of eicosanoids, including the anti-inflammatory lipoxin A4 (LXA4). Nevertheless, the impact of 12/15-LO on chronic inflammatory diseases such as arthritis has remained elusive. By using two experimental models of arthritis, the K/BxN serum-transfer and a TNF trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
87
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 141 publications
(94 citation statements)
references
References 44 publications
7
87
0
Order By: Relevance
“…34 Recently, the anti-inflammatory and tissue protective role of 12/15-LOX and LXA 4 axis in regulating TNF␣ were confirmed and demonstrated in two murine arthritis models. 29 This is also the initial LOX in the biosynthesis of D-series Rv and PD. The potent actions of SPM in disease models in vivo are summarized in Table 1 8 73 The first evidence was obtained for the conversion of DHA to unknown DHA-derived products in 1984 in retinal pigment cells using radiolabeled DHA and inhibitors.…”
Section: Resolvins and Protectinsmentioning
confidence: 99%
See 2 more Smart Citations
“…34 Recently, the anti-inflammatory and tissue protective role of 12/15-LOX and LXA 4 axis in regulating TNF␣ were confirmed and demonstrated in two murine arthritis models. 29 This is also the initial LOX in the biosynthesis of D-series Rv and PD. The potent actions of SPM in disease models in vivo are summarized in Table 1 8 73 The first evidence was obtained for the conversion of DHA to unknown DHA-derived products in 1984 in retinal pigment cells using radiolabeled DHA and inhibitors.…”
Section: Resolvins and Protectinsmentioning
confidence: 99%
“…Resolution of inflammation involves many cellular and tissue processes, including apoptosis, phagocytosis, cytokine/chemokine profiles and their scavenging mechanisms, as well as lymphatic drainage; 22 these will not be addressed herein (for these, interested readers are directed to refs. [22][23][24][25][26][27][28][29][30]. This review focuses on new concepts relevant in the pathophysiology of the fundamental process of resolution of acute inflammation born from uncovering novel endogenous lipid mediators in the author's laboratory that are controllers that activate endogenous anti-inflammation and proresolution circuits.…”
Section: New Solution For Resolution Of Acute Inflammationmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, although the activation of the ALOX5/ALOX5AP complex is key to leukotriene synthesis, it can alternatively lead to the biosynthesis of other compounds, such as lipoxins (16). The intermediate LTA 4 can be converted to lipoxin A4 (LXA 4 ) (5S, 6R, 15S-trihydroxy-eicosa-7E, 9E, 11Z, 13E-tetraenoic acid) by action of 12-lipoxygenase (ALOX12) in humans (17,18) or in mice by arachidonate 15-lipoxygenase (ALOX15 or ALOX12/15) (19,20).…”
mentioning
confidence: 99%
“…Although 12/15-lipoxygenase has been reported to be anti-inflammatory in mouse knockout models of rheumatoid arthritis or peritonitis (41,42), other studies have suggested proinflammatory roles of 12/15-lipoxygenase and 12(S)-HETES or 15(S)-HETE in obese adipose tissue (43) or vascular endothelial cells (27,44). Studies in 12/15-lipoxygenase-deficient murine peritoneal macrophages showed 12/15-lipoxygenase to augment toll-like receptor-induced expression of IL-12 (28), potentially involving interferon regulatory factor 8.…”
Section: Discussionmentioning
confidence: 99%